Bill O'Reilly's Legends & Lies: The Real West - Fisher, David 1946-; O'Reilly, Bill (New York : Henry Holt and Company, 2015)
"How did Davy Crockett save President Jackson's life--only to end up dying at the Alamo? Was the Lone Ranger based on a real lawman--and was he an African American? What amazing detective work led to the capture of Black Bart, the 'gentleman bandit' and one of the West's most famous stagecoach robbers? Did Butch Cassidy and the Sundance Kid really die in a hail of bullets in South America? Generations of Americans have grown up on TV shows, movies, and books about these Western icons. But what really happened in the Wild West?"--
Daniel Boone : traitor or patriot? -- David Crockett : Capitol hillbilly -- Kit Carson : duty before honor -- Black Bart : gentleman bandit -- Wild Bill Hickok : Plains justice -- Bass Reeves : the real Lone Ranger -- George Armstrong Custer : a general's reckoning -- Buffalo Bill and Annie Oakley : the radical opportunists -- Jesse James : bloody politics -- Doc Holliday : desperate measures -- Billy the Kid : escape artist -- Butch Cassidy : the last man standing.
Includes bibliographical references.
Keywords: Frontier and pioneer life -- Anecdotes -- West (U.S.); HISTORY / United States / State & Local / West (AK, CA, CO, HI, ID, MT, NV, UT, WY).; HISTORY / United States / 19th Century; West (U.S.) -- Biography; West (U.S.) -- Anecdotes -- History